Migration and community in Bronze Age Orkney: innovation and continuity at the Links of Noltland. (June 2022) - Moore, Hazel; Wilson, Graeme; Ni Challanain, Mairead; McCormick, Maeve; Marshall, Peter D.; Dulias, Katharina; Foody, M. George B.; Justeau, Pierre; Pala, Maria; Richards, Martin B.; Edwards, Ceiridwen J.
Abstract: Abstract : The remarkable archaeological record of Neolithic Orkney has ensured that these islands play a prominent role in narratives of European late prehistory, yet knowledge of the subsequent Bronze Age is comparatively poor. The Bronze Age settlement and cemetery at the Links of Noltland, on the island of Westray, offers new evidence, including aDNA, that points to a substantial population replacement between the Late Neolithic and Bronze Age. Focusing on funerary practice, the authors argue for interconnecting identities centred on household and community, patrilocality and inheritance. The findings prompt a reconsideration of the Orcadian Bronze Age, with wider implications for population movement and the uptake of cultural innovations more widely across prehistoric north-western Europe.